A measurement of ∆Γs - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Langenbruch, Christoph; et al. (Journal of high energy physics, 2024)
Using a dataset corresponding to 9 fb−1 of integrated luminosity collected with the LHCb detector between 2011 and 2018 in proton-proton collisions, the decay-time distributions of the decay modes B0s → J/ψη′ and B0s → J/ψπ+π− are studied. The decay-width difference between the light and heavy mass eigenstates of the B0s meson is measured to be ∆Γs = 0.087 ± 0.012 ± 0.009 ps−1, where the first uncertainty is statistical and the second systematic